Posterior Reversible Encephalopathy Syndrome : A Rare Cause of Sudden Onset Vision Loss in Pregnancy - Chaudhary, R; Dadhich, S; Vyas, J (Nepal Journal of Obstetrics and Gynaecology, 2012)
Posterior Reversible Encephalopathy Syndrome (PRES) is a very rare cause of sudden onset vision loss in pregnancy. There are only few case reports in literature. It is characterized by headache, seizures, altered mental status and visual deficits ranging from visual neglect to cortical blindness. Here a case if PRES has been reported with discussion on its pathophysiology. NJOG 2011 Nov-Dec; 6 (2): 51-52 DOI: http://dx.doi.org/10.3126/njog.v6i2.6759